An experimental study on the perception of violin bow mass distribution - Salvador-Castrillo Víctor; Picard Amélie; Spalletta Duilio; Ablitzer Frédéric; Fritz Claudia (Acta Acustica)
The goal of this study is to investigate the perception of different bow mass distributions using an experimental violin bow. The position of the centre of mass and the moment of inertia were independently modified through five distinct mass configurations, which were tested by multiple violinists. Various perceptual tests, including three discrimination tests and a free evaluation test, were conducted. Concepts from Signal Detection Theory were used to calculate a representative sensitivity value, considering participants’ sureness in their responses to discrimination tests. Results indicate that participants were sensitive to a substantial variation (10%) in the position of the centre of mass when holding the bow in the air versus during playing, though they did not seem to perceive minor changes (4%) significantly. Conversely, participants exhibited sensitivity to both minor (4%) and substantial (12%) variations in the moment of inertia while playing, suggesting a heightened awareness of even slight modifications in this parameter. Furthermore, the free evaluation test revealed that the perceived bow weight was influenced by both parameters, while the quality of bouncing bow strokes appeared to be more influenced by the moment of inertia.